Primary cerebral malignant melanoma: A case report with literature review. Issue 4 (January 2017) - Tang, Kai; Kong, Xiangyi; Mao, Gengsheng; Qiu, Ming; Zhu, Haibo; Zhou, Lei; Nie, Qingbin; Xu, Yi; Du, Shiwei
Abstract : Abstract: Primary intracranial melanomas are uncommon and constitute approximately 1% of all melanoma cases and 0.07% of all brain tumors. In nature, these primary melanomas are very aggressive and can spread to other organs. We report an uncommon case of primary cerebral malignant melanoma—a challenging diagnosis guided by clinical presentations, radiological features, and surgical biopsy results, aiming to emphasize the importance of considering primary melanoma when making differential diagnoses of intracranial lesions. We present a rare case of a primary cerebral melanoma in the left temporal lobe. The mass appeared iso-hypodense on brain computed tomography (CT), short signal on T1-weighted magnetic resonance images (T1WI) and long signal on T2WI. It was not easy to make an accurate diagnosis before surgery. We showed the patient's disease course and reviewed related literatures, for readers' reference. Written informed consent was obtained from the patient for publication of this case report and any accompanying images. Because of this, there is no need to conduct special ethic review and the ethical approval is not necessary. After surgery, the pathological examination confirmed the diagnosis of melanoma. The patient was discharged without any complications and went on to receive adjuvant radiochemotherapy. It is difficult to diagnose primary cerebral melanoma in the absence of any cutaneous melanosis. A high index of clinical suspicion along with good pathology reporting is the key in diagnosing these extremely rare tumors.